EFEKTIVITAS MATA KULIAH PANCASILA UNTUK PENGUATAN KARAKTER MAHASISWA DI UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
Character education is an important aspect in developing the affective domain, especially for the next generation of the nation. This article aims to describe the effectiveness of Pancasila courses for strengthening character education for HKBP Nommensen Pematangsiantar University students. The writing of this article uses qualitative data analysis in which the data obtained for the study comes from questionnaires, interviews, and observation notes. The results of this study are known that the ethical level of students at HKBP Nommensen Pematangsiantar University is quite good. Student independence and discipline in Pancasila courses are closely related to how students get used to being actively involved and being part of character strengthening. The intensity of students in participating in Pancasila course activities is also influenced by factors of honesty, responsibility, concern, and communication that respects each other in the face-to-face or online process.